4(6-2y)-4y=6

Move all terms not containing y to the right side of the equation.

Subtract 24 from both sides of the equation.

-12y=6-24

Subtract 24 from 6.

-12y=-18

-12y=-18

Divide each term by -12 and simplify.

Divide each term in -12y=-18 by -12.

-12y-12=-18-12

Cancel the common factor of -12.

Cancel the common factor.

-12y-12=-18-12

Divide y by 1.

y=-18-12

y=-18-12

Cancel the common factor of -18 and -12.

Factor -6 out of -18.

y=-6(3)-12

Cancel the common factors.

Factor -6 out of -12.

y=-6⋅3-6⋅2

Cancel the common factor.

y=-6⋅3-6⋅2

Rewrite the expression.

y=32

y=32

y=32

y=32

y=32

The slope-intercept form is y=mx+b, where m is the slope and b is the y-intercept.

y=mx+b

Find the values of m and b using the form y=mx+b.

m=0

b=32

The slope of the line is the value of m, and the y-intercept is the value of b.

Slope: 0

y-intercept: 32

Slope: 0

y-intercept: 32

Graph 4(6-2y)-4y=6